Education for sustainability: The position of Iceland - Gunnarsdóttir, Bryndís Sóley; Árnadóttir, Sólveig María; Guðmundsson, Bragi; Jónsson, Ólafur Páll (Menntavísindasvið Háskóla Íslands, 2021)
The subject of this article is education for sustainable development in Iceland. The article is based on the authors’ master’s project written in the spring of 2020 (Bryndís Sóley Gunnarsdóttir & Sólveig María Árnadóttir, 2020). The authors are participants in a research project under the auspices of the Nordic Council of Ministers, led by Iceland. The aim of the study is to map the situation in the Nordic countries in connection with the implementation of UN Sustainable Development Goal 4.7 on education for sustainability. The key concepts of the goal are sustainability and sustainable development, human rights, gender equality, cultural diversity and global awareness.The UN Sustainable Development Goals aim to lead to a better life, living conditions and environment. The UN member states are committed to implementing them during their period of validity. There are a total of 17 goals and 169 sub-goals. As many other countries, Iceland has had to set clear goals in order to achieve them. Icelandic education policy stipulates the importance of sustainability, this being one of the basic elements of education that should be integrated into all school work.This article seeks to answer two research questions: 1) What do laws and regulations in Iceland say about education for sustainability? 2) How do two compulsory schools in Iceland work towards sustainability? In order to answer these questions, data collection was divided into two parts. Firstly, a content analysis was conducted on the Icelandic law on compulsory schools, the Icelandic national curriculum and the educational policy of six municipalities. Secondly, focus group interviews were conducted in two compulsory schools. In each school, three groups were interviewed: 1) school administrators, 2) a focus group of teachers and 3) a focus group of fifteen to sixteen year old students.The results indicate that there is lack of discussion relating to sustainability, human rights, gender equality, global citizenship and appreciation of cultural diversity in ...